2020
DOI: 10.1136/vr.105522
|View full text |Cite
|
Sign up to set email alerts
|

Onset and duration of cis‐atracurium neuromuscular block during fentanyl and lidocaine infusions in isoflurane‐anaesthetised dogs

Abstract: BackgroundThis retrospective study assessed the onset and duration of the neuromuscular block (NMB) induced by cis-atracurium 0.15 mg/kg intravenously with and without fentanyl or lidocaine infusions in 45 isoflurane-anaesthetised dogs.MethodsDogs with neuromuscular function assessed by a calibrated train-of-four (TOF) monitor with stimulation (every 13 s) of the peroneal nerve were included. The onset and duration of the NMB were defined as the time from cis-atracurium administration until TOF=0 and the time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…1 For comparison, dogs receiving the same dose (0.15 mg/kg), had an onset time of 2.9 ± 0.8 mins. 5 Data from the latter study indicated that the onset time of the NMB induced by cis-atracurium can be shortened in isoflurane-anaesthetised dogs administered fentanyl and lidocaine. 5 It can also be influenced by others drugs that affect muscle contractility and/or cardiac output, such as benzodiazepines, 6 acepromazine, 7 alpha-2 adrenoceptor agonist drugs, 7,8 propofol 9,10 and inhalant agents.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…1 For comparison, dogs receiving the same dose (0.15 mg/kg), had an onset time of 2.9 ± 0.8 mins. 5 Data from the latter study indicated that the onset time of the NMB induced by cis-atracurium can be shortened in isoflurane-anaesthetised dogs administered fentanyl and lidocaine. 5 It can also be influenced by others drugs that affect muscle contractility and/or cardiac output, such as benzodiazepines, 6 acepromazine, 7 alpha-2 adrenoceptor agonist drugs, 7,8 propofol 9,10 and inhalant agents.…”
Section: Discussionmentioning
confidence: 91%
“…5 Data from the latter study indicated that the onset time of the NMB induced by cis-atracurium can be shortened in isoflurane-anaesthetised dogs administered fentanyl and lidocaine. 5 It can also be influenced by others drugs that affect muscle contractility and/or cardiac output, such as benzodiazepines, 6 acepromazine, 7 alpha-2 adrenoceptor agonist drugs, 7,8 propofol 9,10 and inhalant agents. 10,11 To date, there has been no study in cats comparing cisatracurium and different anaesthetic protocols.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…If needed, blockages that showed a duration longer than reported for the canine species [ 5 ] could be antagonized with IV atropine 0.04 mg kg −1 (Atropine Solfato 1 mg mL −1 ATI, Italy) injected 1 min before 0.1 mg kg −1 neostigmine (Prostigmina ® 0.5 mg mL −1 MEDA Farma SpA, Milano, Italy). Potential side effects were appropriately treated.…”
Section: Methodsmentioning
confidence: 99%
“…In canine practice, neuromuscular-blocking agents (NMBs) have been used in different procedures: ophthalmological procedures (to prevent extraocular muscle contraction and produce a relaxed globe in a central position and reduce the risk of vitreous expansion), thoracotomy, laparotomy, ovariohysterectomy, castrations, diaphragmatic-hernia repair, portosystemic shunts, etc. [ 3 , 4 , 5 ]. Authors showed that NMB-induced neuromuscular blockade is potentiated and prolonged when halogenated anesthetics are used; in addition, inhalational anesthetics increase the neuromuscular blockade produced by nondepolarizing drugs in a dose-dependent manner [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%